2016
DOI: 10.1111/crj.12517
|View full text |Cite
|
Sign up to set email alerts
|

Association of eNOS and ACE gene polymorphisms and plasma nitric oxide with risk of non‐small cell lung cancer in South India

Abstract: We report for the first time that polymorphisms in the eNOS "A/A" (homozygous mutant) and ACE "I/D" genotypes might contribute to the increased risk of NSCLC in the South Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
0
13
1
Order By: Relevance
“…In recent two decades, polymorphisms of eNOS gene have gained attention for susceptibility of tumorigenesis or carcinogenesis, as well as cancer invasion and metastasis. Several studies focused on the associations of its three major polymorphisms, namely G894T, T-786C and VNTR 4a/b, and different cancers, such as bladder 13 - 15 , 22 , colorectum 14 , 15 , 23 , breast 11 , 13 , 14 , 24 - 26 , prostate 14 , 17 , 27 - 33 , stomach 14 , 34 , lung 35 - 41 , liver 10 , 14 , 42 , gallbladder 43 , pancreas 44 , and others 14 , 45 - 47 . There were also different researches investigating correlation of eNOS polymorphisms and responsiveness of different therapies toward malignancies, such as chemotherapy, targeted therapy and radiotherapy 5 , 10 , 38 , 48 - 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent two decades, polymorphisms of eNOS gene have gained attention for susceptibility of tumorigenesis or carcinogenesis, as well as cancer invasion and metastasis. Several studies focused on the associations of its three major polymorphisms, namely G894T, T-786C and VNTR 4a/b, and different cancers, such as bladder 13 - 15 , 22 , colorectum 14 , 15 , 23 , breast 11 , 13 , 14 , 24 - 26 , prostate 14 , 17 , 27 - 33 , stomach 14 , 34 , lung 35 - 41 , liver 10 , 14 , 42 , gallbladder 43 , pancreas 44 , and others 14 , 45 - 47 . There were also different researches investigating correlation of eNOS polymorphisms and responsiveness of different therapies toward malignancies, such as chemotherapy, targeted therapy and radiotherapy 5 , 10 , 38 , 48 - 53 .…”
Section: Discussionmentioning
confidence: 99%
“…And yet, the answer was conflicting so far. One study showed that VNTR polymorphism was the culprit 35 , while another believed high expression of NOS was a favorable prognostic sign 40 . Moreover, Donnini et al also reports that NO and PGE2 exist cross-talk effects in EGFR-driven epithelial tumor cells and may as the better therapeutic strategies for cancer treatment 54 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Han et al (14)found that upregulation of ACE in mice increased the risk of laryngeal cancer. Peddiredy, Vidyullatha and others (15) found that in India, the diversity of ACE and eNOS genes increased the risk of non-small cell lung cancer, and the expression of ACE in lung cancer tissues was lower than that of tissue adjacent to cancer tissues. It is just like Blánaid M Hicks and others (16) found that the use of ACEIs is associated with an increased risk of lung cancer, and this correlation is particularly signi cant in people who have used ACEIs for more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…24 Contrastingly, Peddireddy et al showed a correlation between non-small cell lung cancer and intron 4 27 bp repeat polymorphism in patients with the a/a genotype. 26 Fujimoto et al 27 reported that NOS activity was significantly higher in patients with lung adenocarcinoma than in normal subjects, and most of the total NOS activity in their samples was mediated by structural eNOS. Shaul et al 28 suggested that eNOS may play a role in the development and differentiation of both normal and neoplastic airway epithelium.…”
Section: Enos Gene G894t Genotypementioning
confidence: 99%